Integrating Local Wisdom: Islamic Learning Management via Reyog Puppetry in Early Childhood Education - Alip Sugianto; Sayid Abas (Journal of Early Childhood Education Perspectives, 2026)
Islamic religious education plays a vital role in shaping children’s moral and spiritual foundations from an early age, particularly considering that early childhood is a developmental stage characterized by play, imagination, and active exploration. Integrating religious values into meaningful and enjoyable learning experiences is therefore essential. Aisyiyah Singosaren Kindergarten adopts an innovative approach by utilizing Reyog, a traditional art form from Ponorogo, as a pedagogical medium to instill Islamic values in young learners. This article seeks to examine and understand the management of Islamic religious education learning implemented through the integration of local Reyog Ponorogo culture. The study employs a descriptive qualitative method aimed at systematically describing and analyzing the planning, implementation, and evaluation of Islamic religious education at the kindergarten. Data were collected through classroom observations, documentation review, and in-depth interviews with teachers and school administrators. The findings reveal that learning management begins with careful planning aligned with themes, learning objectives, basic competencies, and measurable indicators. Classroom organization, including learning space arrangement and seating design, supports active engagement. Instructional strategies include lectures, dialogic interaction, and demonstrations. Evaluation is conducted through observation, recall activities, and reinforcement to consolidate children’s understanding of Islamic values.